Social determinants of health and cognitive function: A cross‐sectional study among men without dementia - Kayla B. Corney; Julie A. Pasco; Amanda L. Stuart; Bianca E. Kavanagh; Mohammadreza Mohebbi; Sophia X. Sui; Lana J. Williams (Brain and Behavior, 2023)
Abstract Background Certain age‐related and medical factors have been associated with cognitive dysfunction; however, less is known regarding social determinants of health. The current study aimed to investigate associations between social determinants of health and cognitive function in a population‐based sample of men without dementia. Methods Data were drawn from the ongoing Geelong Osteoporosis Study (n = 536). Cognitive function was determined using the Cog‐State Brief Battery. Area‐based socioeconomic status (SES) was determined using the Index of Relative Socioeconomic Advantage and Disadvantage, marital status by self‐report, and social support by the Multidimensional Scale of Perceived Social Support, which considers family, friends, and significant others. Results Belonging to a higher SES group, being in a relationship (married/de‐facto) and perceived social support from a significant other and friends were each associated with better overall cognitive function. In regard to the specific cognitive domains, higher SES was associated with better psychomotor function and visual learning, being in a relationship was associated with better working memory, and perceived social support from a significant other was associated with better attention and working memory, with perceived social support from friends associated with better psychomotor function. There were no associations detected between social support from family and any of the cognitive domains. Conclusion Higher SES, being in a relationship, and greater perceived social support from a significant other and friends were associated with better cognitive function. Further studies identifying underlying mechanisms linking social factors with cognition are needed to establish prevention strategies and enhance cognitive health.